'Both Directions at Once': Chronos, Aion and the Timelessness of the Unconscious. Issue 1 (February 2022) - Bergsma, Theodore T.
Abstract : This paper advances an interpretation of Deleuze's Chronos–Aion distinction in The Logic of Sense as a development of Freud's thesis concerning the timelessness of the unconscious. If Chronos forms a unidirectional sequence along the arrow of a living present, the Aion as the eternal truth of events represents a form of time that is transcendentally distinct. While Chronos belongs to consciousness through the functions of good and common sense, the paradoxical insistence of the Aion represents for Deleuze the force of the unconscious. By identifying the Aion with the death drive, Deleuze positions timelessness as the transcendental condition of the living, corporeal ego.